Does the Type of Anaerobic Test Matter? A Comparison between the Anaerobic Intermittent Kick Test and Wingate Anaerobic Test in Taekwondo Athletes - Stefanos Boutios; Alessandra di Cagno; Andrea Buonsenso; Marco Centorbi; Enzo Iuliano; Giuseppe Calcagno; Giovanni Fiorilli (MDPI AG, 2022)
The specificity of training as well as the specificity of monitoring the training process are believed to be fundamental principles to efficiently plan and carry out the preparation and performance development of athletes. The Anaerobic Intermittent Kick Test (TAIKT) is a sport-specific field test used to specifically evaluate the anaerobic profile of Taekwondo athletes. The aim of this study was to verify whether TAIKT and the 'gold standard' Wingate Anaerobic test (WAnT) were both efficient means to optimally determine the anaerobic power and anaerobic capacity of Greek Taekwondo athletes at a middle-high technical level. Fifteen athletes, 10 females and 5 males (mean age 23.4 ± 4.14 years), underwent the two anaerobic tests (TAIKT and WAnT). The peak of power, the anaerobic capacity, and the peak of blood lactate (BL) were recorded. The two tests showed a moderate correlation with the r value ranging between 0.353 and 0.428, if applied to a sample of middle-high technical level athletes. Regarding the peak of BL, data indicated 40% concordance between the two tests with a coefficient of variation of 12%. Consequently, the two tests were correlated even if not interchangeable due to the different type of exercise required in these assessments. In conclusion, to assess the anaerobic performances and physiological characteristics of Taekwondo athletes, independently of their technical level, the WAnT resulted suitable, while to better assess the functional performance and specific demands of Taekwondo, the TAIKT is more indicated.